Calcified cyanobacteria from the Upper Ediacaran of South China - Zhong, Yi-jiang; Liu, Gang; Dong, Yi-xin; Algeo, Thomas J. (Frontiers in Marine Science, 2025)
Fossil records of calcified cyanobacteria from the Neoproterozoic are rare despite the high carbonate saturation of contemporaneous seawater. In this study, we report the discovery of calcified cyanobacteria in microbialites from the Upper Ediacaran Dengying Formation in South China, based on integrated field investigations and petrographic analyses of polished surfaces and thin-sections. Scanning electron microscopy (SEM), energy-dispersive X-ray spectroscopy (EDS), and X-ray diffraction (XRD) reveal that filamentous sheath structures are preserved as dense, fine-crystalline dolomite. The tube-like microfossils are identified as the calcified cyanobacteria Girvanella. This discovery fills a gap in the fossil record of microbialite-hosted calcified cyanobacteria spanning the interval from the Cryogenian glaciations to the onset of the Cambrian Period. Petrographic and mineralogical analyses indicate that primary high-Mg calcite, precipitated in vivo within Girvanella sheaths as a likely precursor to microcrystalline dolomite, contributed to the exceptional preservation of these fossils. The sporadic occurrence of calcified cyanobacteria may reflect transient episodes of elevated carbonate saturation driven by fluctuations in seawater chemistry. Concurrently, the possible rapid evolution of CO2-concentration mechanisms (CCMs) may have enhanced the calcification capability of cyanobacteria. Thus, these features foreshadowed the widespread microbial calcification that emerged in the Cambrian.